2013
DOI: 10.1007/s00270-012-0544-4
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Diabetic Foot in a Selected Population of Patients with Below-the-Knee Disease: Is the Angiosome Model Effective?

Abstract: Purpose To evaluate the efficacy of percutaneous transluminal angioplasty (PTA) in a selected population of diabetic patients with below-the-knee (BTK) disease and to analyze the reliability of the angiosome model. Methods We made a retrospective analysis of the results of PTA performed in 201 diabetic patients with BTK-only disease treated at our institute from January 2005 to December 2011. We evaluated the postoperative technical success, and at 1, 6, and 12 months' follow-up, we assessed the rates and valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 41 publications
0
83
0
3
Order By: Relevance
“…of patientsNo. of limbsAgeMale/FemaleEthnicityHTNDLPHistory of smokingESRD/on dialysisCADCVDFossaceca et al, 2013 [36] DR201-75.5 ± 9.5136 M/65 F-124 (62%)--15 (7%)65 (32%)- IR  p -valuesNA----------Söderström et al, 2013 [37] DR22612168.4 ± 11.989 M/32 F-89 (74%)78 (65%)24 (18%)26 (22%)69 (57%)29 (24%) IR12973.8 ± 11.171 M/58 F-102 (79%)84 (65%)20 (24%)13 (10%)90 (70%)24 (19%)  p -valuesNANA0.0010.002-NSNSNS0.0120.044NS DR: propensity score matched pairs-8471.7 ± 11.059 M/25 F-63 (75%)50 (60%)18 (25%)14 (17%)53 (63%)20 (24%) IR: propensity score matched pairs8470.3 ± 10.958 M/26 F-63 (75%)60 (71%)15 (20%)12 (14%)55 (66%)17 (20%)  p -values: propensity score matched pairsNANANSNS-NSNSNSNSNSNSAcín et al, 2014 [38] DR46-72 (63–78)30 M/16 F-31 (67%)13 (28%)36 (78%)Excluded17 (37%)9 (20%) IR ‘through collaterals’22-…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of patientsNo. of limbsAgeMale/FemaleEthnicityHTNDLPHistory of smokingESRD/on dialysisCADCVDFossaceca et al, 2013 [36] DR201-75.5 ± 9.5136 M/65 F-124 (62%)--15 (7%)65 (32%)- IR  p -valuesNA----------Söderström et al, 2013 [37] DR22612168.4 ± 11.989 M/32 F-89 (74%)78 (65%)24 (18%)26 (22%)69 (57%)29 (24%) IR12973.8 ± 11.171 M/58 F-102 (79%)84 (65%)20 (24%)13 (10%)90 (70%)24 (19%)  p -valuesNANA0.0010.002-NSNSNS0.0120.044NS DR: propensity score matched pairs-8471.7 ± 11.059 M/25 F-63 (75%)50 (60%)18 (25%)14 (17%)53 (63%)20 (24%) IR: propensity score matched pairs8470.3 ± 10.958 M/26 F-63 (75%)60 (71%)15 (20%)12 (14%)55 (66%)17 (20%)  p -values: propensity score matched pairsNANANSNS-NSNSNSNSNSNSAcín et al, 2014 [38] DR46-72 (63–78)30 M/16 F-31 (67%)13 (28%)36 (78%)Excluded17 (37%)9 (20%) IR ‘through collaterals’22-…”
Section: Resultsmentioning
confidence: 99%
“…The numerous methodological flaws in three studies [36, 38, 40] leave their results vulnerable to type I and type II errors, making it injudicious to attribute weight to their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mean time to healing was not significantly different in DR compared with IR when analyzed by three studies. One study found a significant increase in amputation-free survival in DR when compared with IR (evaluated by three studies 24,26,27 ). One study that demonstrated a significant difference in wound healing at 12 months with DR was undertaken by Varela et al, 20 however, this group also looked at the effect of collaterals on revascularization.…”
Section: Role Of Direct Revascularization Of An Affected Angiosomementioning
confidence: 97%
“…19,20,[22][23][24][25] Other studies compared the use of DR or IR in their patient series, recording outcomes of each technique and thereby examining whether DR is technically possible and effective for treatment of lower limb ischemic ulceration and, if so, how it compares with the results of IR. 18,21,26,27 Patient comorbidities were included in all studies (Table II). Patients with diabetes were included in all studies and were predominant in nine papers (>80% patients with diabetes).…”
Section: Role Of Direct Revascularization Of An Affected Angiosomementioning
confidence: 99%
“…[8][9][10] This angiosome model (called traditional angiosome in this project) divides the foot into three angiosomes: medial plantar, lateral plantar, and calcaneal angiosomes. These angiosomes are supplied by blood flow from medial plantar, lateral plantar, and medial calcaneal arteries, respectively.…”
mentioning
confidence: 99%